2009
DOI: 10.1029/2008jd010572
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the characteristics of rain events in India

Abstract: [1] Daily gridded (1°Â 1°) rainfall data prepared by the India Meteorological Department for the period have been used in this study to examine possible changes in the frequency of rain events in India in terms of their duration and intensity per day. So far as the duration is concerned, a rain event is classified as short, long, dry, or prolonged dry spell. Similarly in terms of intensity, a rainy day is considered as low, moderate, or heavy. Changes in the frequency of these events have great relevance from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
177
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(187 citation statements)
references
References 20 publications
9
177
1
Order By: Relevance
“…However, it should be mentioned that Goswami et al (2010), in their analysis of daily rainfall data from 15 stations between April and October in NE India, for the period from 1975 to 2006, found a decreasing trend of extreme events with more than 150 mm rainfall per day and that this exceeded the 99th percentile. This is in contrast to a detected increasing trend of such events in central India (Goswami et al 2006) and in the whole of India (Dash et al 2009;Dash et al 2011).…”
Section: Introductioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, it should be mentioned that Goswami et al (2010), in their analysis of daily rainfall data from 15 stations between April and October in NE India, for the period from 1975 to 2006, found a decreasing trend of extreme events with more than 150 mm rainfall per day and that this exceeded the 99th percentile. This is in contrast to a detected increasing trend of such events in central India (Goswami et al 2006) and in the whole of India (Dash et al 2009;Dash et al 2011).…”
Section: Introductioncontrasting
confidence: 50%
“…These stable conditions are seen not only on a regional scale but also at subdivision and station levels (Prokop and Walanus 2003;Dash et al 2012;Jain et al 2013). Dash et al (2009), using highresolution daily gridded rainfall data for the period , examined the changes in the number of rain events of different durations and intensities in the whole of India as well as over its homogeneous regions. They found that the frequency of heavy rain days and moderate rain days increased and decreased, respectively (significant at 5 % level), in northeast India in both the monsoon and post-monsoon seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Goswami et al (2006) found that the frequency and intensity of extreme rainfall increased in central India for the period 1951−2004. Dash et al (2009) demonstrated that heavy precipitation days increased in central northeast and northeast India during the monsoon season for the period 1951−2004, and moderate rain days decreased in these regions. In contrast to Dash et al (2009), Goswami et al (2010 reported that extreme rain event frequency tended to decrease at 15 stations in northeast India from 1975.…”
Section: Introductionmentioning
confidence: 99%
“…Dash et al (2009) demonstrated that heavy precipitation days increased in central northeast and northeast India during the monsoon season for the period 1951−2004, and moderate rain days decreased in these regions. In contrast to Dash et al (2009), Goswami et al (2010 reported that extreme rain event frequency tended to decrease at 15 stations in northeast India from 1975. Shahid (2010 analyzed trends in annual and seasonal precipitation for the period 1958−2007 in Bangladesh, and showed that the annual and pre-monsoon precipitation increased at the rates of 5.53 and 2.47 mm year −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation